Can the Ethical Orientation Mitigate the Manager’s Earnings Management? - Priyastiwi Priyastiwi; Sriwidharmanely Sriwidharmanely; Krisnhoe Fitri Fatjriyati (Journal of Accounting and Investment, 2020)
Research aims: This study investigates the role of the ethical orientation of management in the relationship of asymmetry information and management status toward an individual’s decision-making with respect to earnings management behaviors.Design/Methodology/Approach: This methodology is an experimental method with 2x2 between-subject designs. 55 Accounting students from three private universities participated in 4 scenarios of cases (permanent and contractual management status, high and low asymmetry information) individually. Other side, the ethical orientation is measured, relativist and idealist. The Hypothesis was analyzed by ANOVA.Research findings: The ethical orientation influence managers’ earnings management decisions. It can mitigate the influence of asymmetry information toward manager earning management decisions. Theoretical contribution/ Originality: This research explains that earnings management behavior also can be explained by ethical approach, not only by using agency theory. Decision-makers will use ethical considerations when they are faced by the earnings management practices.Practitioner/Policy implication: The results support pro-social theory that ethical orientation can influence the decision making when individuals are exposed to ethical dilemmas to make earning management.Research limitation/Implication: Participants in this study used students, so they did not have experience. future studies can use professional participants and consider management status in more detail.